2020
DOI: 10.1371/journal.pone.0234478
|View full text |Cite
|
Sign up to set email alerts
|

Reduced 2-year aneurysm retreatment and costs among patients treated with flow diversion versus non-flow diversion embolization: A Premier Healthcare Database retrospective cohort study

Abstract: Introduction The use of endovascular treatments, including Pipeline embolization devices (PEDs) and coiling approaches (non-PEDs), has played an increasingly important role in the treatment of intracranial aneurysms. Despite multiple studies evaluating PEDs, a real-world evaluation of follow-up outcomes and costs remains to be completed. Methods The Premier Healthcare Database (PHD), 2010-2017, was queried to identify patients with unruptured intracranial aneurysms treated endovascularly. Rates of readmission,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Taken together, flow diversion is an economical and effective method for the treatment of intracranial aneurysms [20]. Consequently, we concluded that the total cost was lower and the retreatment hospitalization costs of flow diversion were higher than coil embolization for the treatment of intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Taken together, flow diversion is an economical and effective method for the treatment of intracranial aneurysms [20]. Consequently, we concluded that the total cost was lower and the retreatment hospitalization costs of flow diversion were higher than coil embolization for the treatment of intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 79%
“…Despite the higher retreatment hospitalization costs of flow diversion for intracranial aneurysms, the readmission rates and emergency reassessment rates were lower than coil embolization. Taken together, flow diversion is an economical and effective method for the treatment of intracranial aneurysms [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, previous studies reported that the need for retreatment was equivalent in both groups. 23,26) Although previous studies included small aneurysms, aneurysms in locations other than the ICA, or FD approaches other than the PED, the reported cost of FD treatment was lower than that for coil embolization, 25,34,35,37,[38][39][40][41] especially when 9 or more coils were required during the coil embolization procedure. 34) However, almost all previous studies reported the costs for the entire hospital stay, including device costs.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that retreatment was required less frequently in the PED group, a result similar to that in previous studies. 24,25,36,37) However, all previous studies included small aneurysms or aneurysms in locations other than the ICA. Further, previous studies reported that the need for retreatment was equivalent in both groups.…”
Section: Discussionmentioning
confidence: 99%